Volunteers engagement: a comparative study - Silva Peralta, Yamila Fernanda (2019)
A descriptive / comparative research is presented with the aim of knowing engagement levels in university volunteers and associative organizations volunteers’ groups. The Utrecht Work Engagement Scale was administered; it measures vigor, absorption and dedication scales and engagement levels. The sample of this research was intentional non-probabilistic, composed of (a) volunteers from the National University of Mar del Plata (UNMDP) participating during the last 4 years in extension and volunteering projects and (b) associative organizations volunteers from Mar del Plata. Basic descriptive were calculated and non-probabilistic statistics were applied to compare volunteering groups. Results show critical differences between sex in dedication and vigor, between training levels in vigor and engagement (total score). No critical levels were found between volunteering type, age and seniority as a volunteer.